Gender Norms, Workplace Bias, and Career Mobility: A Mixed-Methods Study of Women in Bida Metropolis - Akanbi, Rabi; Dzukogi, Zakiyyah (Departemen Ilmu Administrasi FISIP UNHAS, 2026)
This study investigates the influence of gender stereotypes on women’s career progression in Bida Metropolis, Niger State, Nigeria. Drawing on Gender Role Theory and Feminist Theory, it examines how culturally embedded beliefs and institutional practices shape women’s access to promotion, training, and professional networks. A convergent mixed-methods design was employed, combining a survey of 398 respondents with qualitative interviews and focus group discussions. Quantitative data were analyzed using descriptive statistics, cross-tabulation, and the Chi-square test of independence. The findings reveal statistically significant relationships between gender stereotypes and key career outcomes, including promotion bias (χ² = 45.21, p < .001), limited access to training (χ² = 39.58, p < .001), and exclusion from professional networks (χ² = 18.73, p < .001). A significant gender difference was also observed in promotion experiences (χ² = 6.52, p = .011), with women more likely to report being overlooked. Qualitative evidence indicates that women adopt adaptive strategies such as enhanced performance, mentorship engagement, and peer support to navigate these barriers. The study concludes that gender stereotypes operate through both cultural and structural mechanisms to constrain women’s career advancement. It recommends institutional reforms, equitable access to professional development, and targeted awareness initiatives to promote gender-inclusive workplaces.